THE EFFECT OF TEACING TECHNIQUE AND CRITICAL THINKING TOWARDS STUDENTS’ WRITING SKILL - Ermina Ermina (INFERENCE: Journal of English Language Teaching, 2018)
Abstract. The purpose of this research was to: determine the interactive effect of teaching technique and critical thinking towards students’ writing skill. The research method used was experimental one. Sample size of 80 students consisted of 40 for experiment class from SMK PGRI Sukamulya and 40 from SMK Bani Usman Manunggal for control class. The sampling technique used was cluster sampling. Research instruments were used to test the results of critical thinking (30 items) and writing skill scoring that had been tested valid and reliable. The used test was two-way ANOVA analysis the result showed: (1) There is a significant effect of teaching technique towards students’ writing skill at Private Vocational High School in Tangerang. It is proved by the value of sig 0,000 < 0,05 and Fo = 77,449. (2) There is a significant effect of critical thinking towards students’ writing skill at Private Vocational High School in Tangerang. It is proved by the value of sig 0,000 < 0,05 and Fo = 51,791. (3) There are any significant interactive effects of teaching technique and critical thinking towards students’ writing skill at Private Vocational High School in Tangerang. It is proved by the value of sig 0,033 < 0,05 and Fo = 4,725. This suggests that teaching technique and critical thinking contribute to the improvement of students writing skill.Keyword: Teaching Technique, Critical Thinking, Writing Skill